2007
DOI: 10.1002/mame.200600442
|View full text |Cite
|
Sign up to set email alerts
|

New Photocurable Acrylic/Silsesquioxane Hybrid Optical Materials: Synthesis, Properties, and Patterning

Abstract: Synthesis, properties, and patterning of new acrylic/silsesquioxane hybrid materials are reported. PMA‐functionalized PHSSQ was synthesized by hydrosilylation and then formulated with acrylate monomer mixtures to yield the photocurable materials. Experiments suggest that the thermal/mechanical properties of the parent acrylic polymers could be significantly enhanced by incorporating nano‐sized silsesquioxane moieties. The refractive index and optical loss were reduced by increasing the silsesquioxane content. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…Organic polymer/silica hybrids often increase thermal stability, surface planarity and optical transparency as compared with the corresponding organic polymers [12][13][14]. In our previous work, PI-silicone copolymer afforded negative-tone pattern by RDP using tetramethylammonium hydroxide/water/NMP/methanol as developer [15].…”
Section: Introductionmentioning
confidence: 99%
“…Organic polymer/silica hybrids often increase thermal stability, surface planarity and optical transparency as compared with the corresponding organic polymers [12][13][14]. In our previous work, PI-silicone copolymer afforded negative-tone pattern by RDP using tetramethylammonium hydroxide/water/NMP/methanol as developer [15].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen silsesquioxane (HSQ) as one of POSS monomers had been attracted increasing interest in scientific research and technological innovation 15–20. HSQ could be used as Si/SiO 2 film precursor,21 negative resist,22 and low‐k material 23.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, inorganic–organic hybrid coatings are widely used as interfacial modifiers to improve the properties such as adhesion, barrier properties, and mechanical strength 4, 13–17. Cubic silsesquioxanes (CSSQ) possess unique characteristics with a well‐defined, three‐dimensional nanostructure containing silica cage and the organic functional groups on the silica cage surface with a diameter range of 0.5–1.5nm 18–21.…”
Section: Introductionmentioning
confidence: 99%
“…For example, methacrylate‐functionalized CSSQ‐based dental restorative composites, prepared via photoinitiated free radical polymerization, are found to improve mechanical strength 26. Su et al17 reported that thermal mechanical properties of acrylic polymers were subsequently enhanced by incorporating nanosized polysilsesquioxane. In the present work, multifunctional epoxy monomers and oligomers including epoxy‐functionalized CSSQ were polymerized cationically by UV radiation in the presence of cationic photoinitiator, particularly, for application in lenses.…”
Section: Introductionmentioning
confidence: 99%